Sustainable Use of Calathea lutea in Handicrafts: A Case Study from the Amanã Sustainable Development Reserve in the Brazilian Amazon - Leoni, Juliana Menegassi; Capelotto Costa, Flávia Regina (Economic Botany, 2013)
Sustainable Use ofCalathea luteain Handicrafts: A Case Study from the Amanã Sustainable Development Reserve in the Brazilian Amazon. This study evaluated the local harvest and use of Calathea lutea, an herb used in basket weaving by residents of floodplain communities in the Amanã Sustainable Development Reserve (RDSA). C. lutea is associated with early successional stages of secondary vegetation or abandoned fields, often found alone in monospecific stands, called cauaçuzais. We describe the biology and ecology of C. lutea, including distribution, abundance, and resource availability using GIS and field inventory methods. We measured the area of each surveyed and georeferenced C. lutea stand and estimated the production and consumption of mature stalks in this area. With this information, we estimated the current status of the extractive use of this plant. C. lutea grows vigorously and flowers continuously with an average of 1,699 (+/- 754) clumps ha-1 in the stands. The total 41 georeferenced stands cover an area of 26 ha, with an estimated 44,200 clumps and 850,000 mature stalks. In 2006, approximately 15,000 mature stalks were used by artisans, about 2 % of the available stock. Therefore, the present stock meets artisanś demand with no evidence that the species is suffering from overharvesting. We also observed that the species inhibits plant succession due to its high capacity for dispersal, colonization, and permanence in secondary areas. It has, as a result, colonized about 50 % of high floodplain (várzea) areas formerly converted to agricultural fields in two of the four communities surveyed in this study. To establish more productive and healthy agroecosystems, we suggest enrichment of fallows with fruit and wood producing trees where C. lutea is less exploited. © 2013 The New York Botanical Garden.
Keywords: Calathea Lutea; Orithyia (angiosperm)